CHALLENGES AND OPPORTUNITIES FOR LEARNING SOCIAL SCIENCES IN THE DIGITAL AGE - Audry, Fadilani; Dora, Nuriza (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the challenges and opportunities for digital era social studies learning at SMP Negeri 39 Medan. Rapid technological advances open up opportunities and challenges to integrate technology into the learning process as a way to improve the quality of learning. This study aims to determine the challenges and opportunities for digital era social studies learning at SMP Negeri 39 Medan. This study uses a qualitative approach with a descriptive analysis method. Data were collected through observation, interviews, and documentation. The subjects of the study included the principal, social studies teachers, and students of SMP Negeri 39 Medan. The results of the study showed that there were challenges such as technological gaps, lack of teacher readiness, lack of infrastructure and a less conducive school environment. There are also opportunities such as making it easier for teachers to teach, making it easier to access learning without being hindered by distance or time, students becoming more active and creative, learning becoming more interesting, and opportunities to create digital classes that are planned to be realized in the new school year.